Sorting Through Performance Evaluations: The Influence of Performance Evaluation Reform on Teacher Attrition and Mobility. (December 2020) - Rodriguez, Luis A.; Swain, Walker A.; Springer, Matthew G.
The federal Race to the Top initiative signified a shift in American education policy whereby accountability efforts moved from the school to the teacher level. Using administrative data from Tennessee, we explore whether evaluation reforms differentially influenced mobility patterns for teachers of varying effectiveness. We find that the rollout of a statewide evaluation system, even without punitive consequences, was associated with increased turnover; however, there was comparably greater retention of more effective teachers, with larger differences in turnover between highly and minimally effective teachers confined to urban districts and low-performing schools. These results imply that states and districts can increase exit rates of low-performing instructors in the absence of automatic dismissals, which is a pattern that our analyses suggest may not generalize beyond urban school settings.